Pengaruh Pendampingan Dan Pemberdayaan Masyarakat Terhadap Penerapan Protokol Kesehatan Dan Menyikat Gigi Malam Hari Pada Masa Pandemi (Sistem Monitoring Melalui Daring) - Endah Aryati Ekoningtyas; Hermien Nugraheni; Benni Benyamin (Jurnal Kesehatan Gigi, 2020)
Community empowerment is an effort to provide power (empowerment) or strengthening (strengthening) to the community. Community empowerment is defined as the ability of individuals in the community forum to build community empowerment which aims to find new alternatives in community development. During a pandemic, family participation as a promotive, preventive and preventive approach is needed through the role of one family member to become mentoring whom a role model for the family to break the chain of Covit-19 disease. The research objective was to determine the effectiveness of the development of counseling through community empowerment with the approach of establishing Kader Mandiri Keluarga (KMK) as "Self-Screening Supervisor to Healthy and Night Toothbrushes".The analytical method used is descriptive quantitative, with a sample of 20 mother as a supervisor that representing 20 families. The implementation stages begin with socialization and counseling on the application of a lifestyle as a link breaker in the Covid-19 disease chain. Then every week for a month, questionnaires were distributed about the behavior of implementing health protocols and the behavior of brushing teeth before going to bed at night using a google form which was monitored every week via the WhatsApp group.The differences in behavior changes in control of healthy teeth maintenance from week 1, 2, 3 and week 4 were analyzed using the statistical test used, namely the Friedmen test. The results of the activity showed that there was a significant change in behavior in relation to brushing your teeth for 2 minutes and brushing your teeth before going to bed from week 1, 2, 3 to week 4 (p: 0.05). The role of mentoring activities as an effort to empower the community plays a role in improving and changing general health and dental behavior. The obstacle faced by the facilitator is that it is still difficult to change the mindset of the community in order to be more independent and not depend on the assistant.. Keywords : Mentoring, KMK, supervisors, behavior change